Transgénero: Un análisis desde la mirada de los derechos humanos: Transgender: An analysis from the point of view of human rights - Cedeño Barreto, Mercedes de Los Ángeles (Revista de Ciencias Sociales, 2021)
Sometimes talking about human rights is easy as they are considered universal and they imply a commitment by society to promote healthy coexistence among people, however, it is important to study to what extent transgender people can feel satisfied when they are treated with respect, equality , taking care of their dignity and integrity, freedom, not being discriminated against due to the condition they experience in terms of their sexual identity. The objective is to analyze transgender from a human rights perspective. Oriented with a documentary, descriptive, analytical methodological perspective, addressing considerations related to the subject. It is developed taking into account the essence of the transgender person in their daily life, with their family, the social environment where they develop, finding the support of their parents and that is when they begin to feel good, because it is one of the greatest sufferings they face knowing that they can be disappointed. From a legal point of view, some countries are establishing laws, determining respect for these people. The analysis concludes some achievements such as accepting equal marriage; Furthermore, it is a health issue, for which surgical, clinical, and psychological intervention should be considered; also, existence of some agreements that favor this group.